1992
DOI: 10.1002/j.1552-4604.1992.tb03810.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Pentoxifylline on Red Blood Cell Deformability

Abstract: The proposed mechanism of action for pentoxifylline's beneficial effect in peripheral vascular disease is an improvement in red blood cell deformability. Likewise, single doses of pentoxifylline in healthy volunteers have been shown to improve whole blood filterability, which was suggested to occur as a result of augmented red blood cell deformability. To further assess this, the authors studied the effects of short-term pentoxifylline administration (400 mg three times daily for 7 days) on red blood cell defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Among the drugs affecting the rheological properties of blood, only pentoxifilline should improve the elasticity of red cells but there have also been reports denying such effect [14] or even any role of this drug in the secondary prevention of cerebral ischaemia [15]. On the other hand, the protective mechanisms of feedback may turn out to be very important [16].…”
Section: Discussionmentioning
confidence: 99%
“…Among the drugs affecting the rheological properties of blood, only pentoxifilline should improve the elasticity of red cells but there have also been reports denying such effect [14] or even any role of this drug in the secondary prevention of cerebral ischaemia [15]. On the other hand, the protective mechanisms of feedback may turn out to be very important [16].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also have shown that PTX increases RBC deformability (RBCD) in normal human patients and that pretreatment with PTX can prevent the decrease in RBCD observed in blood circulated through bypass machines during open heart surgery 19 . The results of these latter studies are controversial, however, in that other studies have shown no effect of PTX on human RBCD 20,21 …”
mentioning
confidence: 99%